Event Reviews. Issue 2 (1st September 2017) - Hawkins, Ella; Lennox, Patricia; McNeil, Peter
The Tempest, directed by Gregory Doran for the Royal Shakespeare Company, designed by Stephen Brimson Lewis, 28 November 2016Shakespeare in Ten Acts, The British Library, London, Curated by Zoë Wilcox, Tanya Kirk and Greg Buzwell, 15 April–6 September 2016 Star Makers – Behind the Scenes: The Golden Age of Finnish Cinema, Logomo Arts Centre, Turku, Finland, curated by Joanna Weckmann, 6 April–13 August 2017